PWE-059 A study of patients with cirrhosis admitted to non-transplant general intensive care: prevalence, case mix, outcomes and evaluation of critical illness and disease specific scoring systems. (23rd September 2015) - Thomson, S J; Moran, C; Cowan, M L; Musa, S; Beale, R; Treacher, D; Hamilton, M; Grounds, M; Rahman, T M
Abstract : Introduction: Hospital admission rates attributable to cirrhosis are increasing in the UK. The evidence base for the outcome of critically ill patients with cirrhosis admitted to intensive care (ICU) is currently limited to data from tertiary transplant centres that report mortality rates of between 45 and 74%. We hypothesised that the disease cohort experienced in secondary care is less severe than that reported in the literature and would subsequently demonstrate lower mortality. We report the prevalence, case mix and outcomes of a dual centre ICU study in London. Methods: Data were collected prospectively from two large non-transplant general ICUs in London (St George's and St Thomas' Hospitals) over 20 months (November 07–June 09). All ICU admissions were screened for cirrhosis. Clinical data were recorded to calculate and evaluate the performance of several critical illness and disease specific scoring systems (APACHE II, SAPS II, SOFA, Child Pugh, MELD, UKELD, Glasgow Alcoholic Hepatitis Score and the Royal Free Hospital (RFH) score). Study endpoints were ICU and Hospital mortality. Results: Cirrhosis accounted for 3.3% (137/4198) of ICU admissions. In 118 patients meeting inclusion criteria ICU and hospital mortality rates were 38% and 47%, respectively. Median (IQR) age was 50 (43–59) years, 68% were male, median length of ICU stay was 4.5 (2–10) days and 72% had alcoholic cirrhosis. Median Child Pugh score at presentation was 10 (8–11) (45% Grade A/B), MELD 18 (12–24) and APACHE II 16 (13–22). Hospital mortality was 24% in Child Pugh grade B and 66% in grade C. After multivariate analysis the factors independently predictive of mortality were bilirubin, INR, urea, bicarbonate and pO2 /FiO2 ratio. AUROC for the scoring systems ranged from 0.76 (UKELD) to 0.81 (RFH) for the prediction of mortality outcome. Renal failure (OR 3.4 (1.4–8.4)) and renal replacement therapy during admission (OR 9.6 (3.7–24.8)) had strong associations with mortality. Intubation for gastrointestinal bleeding OR 0.4 (0.1–1.3) was associated with a trend towards better outcome than intubation for respiratory failure OR 2.7 (1.0–7.0). Conclusion: The mortality rates and disease stage reported here are lower than those described in the established literature. Data from specialist transplant centres should not be applied to the patient cohorts seen in general ICUs. We urge critical care physicians to carefully consider the individual clinical case when deciding on ICU admission and not apply potentially misrepresentative figures from previous data sets.